2019
DOI: 10.1101/764001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic Characterization of Posttraumatic Stress Disorder in a Large US Military Veteran Sample

Abstract: Individuals vary in their liability to develop Posttraumatic Stress Disorder (PTSD), the symptoms of which are highly heterogeneous, following exposure to life-threatening trauma. Understanding genetic factors that contribute to the biology of PTSD is critical for refining diagnosis and developing new treatments. Using genetic data from more than 250,000 participants in the Million Veteran Program, genomewide association analyses were conducted using a validated electronic health record-based algorithmically-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 101 publications
0
25
0
Order By: Relevance
“…Analysis of regulation of EXT genes revealed substantial overlap with genes known to be regulated in neuropsychiatric disease. Notably, the CRH receptor (CRHR1) has now been associated with PTSD symptoms, anxiety disorders, and alcohol habitual use in large-scale GWAS studies [11][12][13][14] . In addition, prior work in GWAS association of pathways across psychiatric disorders has demonstrated that the protein encoded by CREB1 directly interacted with several risk genes of psychiatric disorders identified by GWAS 66 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of regulation of EXT genes revealed substantial overlap with genes known to be regulated in neuropsychiatric disease. Notably, the CRH receptor (CRHR1) has now been associated with PTSD symptoms, anxiety disorders, and alcohol habitual use in large-scale GWAS studies [11][12][13][14] . In addition, prior work in GWAS association of pathways across psychiatric disorders has demonstrated that the protein encoded by CREB1 directly interacted with several risk genes of psychiatric disorders identified by GWAS 66 .…”
Section: Discussionmentioning
confidence: 99%
“…As an example, PTSD has been repeatedly associated with a failure to recover from traumatic events, conceptualized as a failure to extinguish learned fear [8][9][10] . Notably, the largest-to-date genomewide association study (GWAS) for PTSD recently found genome-wide level associations between variants of CRHR1, the gene encoding corticotropin-releasing hormone (CRH) receptortype 1, genetically regulated brain-specific CRHR1 expression, and PTSD diagnosis and symptom clusters 11,12 , along with its identification in large GWAS of anxiety and habitual alcohol use 13,14 .…”
mentioning
confidence: 99%
“…These factors may alter the way the disorder overlaps genetically with MDD. As shown in Table 1, at least a quarter of the sample had been exposed to combat (Stein et al, 2020). Another factor to consider is the demographics of the sample, which overly represents males (94.4%), unlike the UK Biobank, PGC 1.5 and is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint The copyright holder for this this version posted November 27, 2020. ; https://doi.org/10.1101/2020.11.25.20229757 doi: medRxiv preprint PGC samples, which have an almost even sex division.…”
Section: Merits and Limitationsmentioning
confidence: 99%
“…[10][11][12][13][14][15] In psychiatry, GWAS have uncovered a high degree of polygenicity underlying mental illnesses and related complex phenotypes. 8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Polygenicity describes the contribution of many single nucleotide polymorphisms (SNPs) with relatively small effect sizes to phenotype development. This phenomenon is ubiquitously observed in psychiatric disorders and comorbid phenotypes, as evidenced by the detection of tens to hundreds of genome-wide significant (GWS) linkage disequilibrium (LD) independent loci.…”
Section: Introductionmentioning
confidence: 99%